Technical report. - Coastal Engineering Research Center (U.S.) (For sale by the Supt. of Docs., U.S. Govt. Print. Off., 1941)
Includes various editions of some numbers.
Includes various editions of some numbers.
No. 4, 1st ed. (1954) accompanied by a supplement: Corrections, revisions and addenda, 1957
No. 1- issued by the U.S. Beach Erosion Board.
Keywords: Shore protection. / fast / http://id.worldcat.org/fast/1116978; Beach erosion. / fast / http://id.worldcat.org/fast/829084; Shore protection / United States.; Beach erosion / United States.; United States. / fast / http://id.worldcat.org/fast/1204155